Damage control operations in non-trauma patients: defining criteria for the staged rapid source control laparotomy in emergency general surgery. Issue 1 (December 2016) - Becher, Robert; Peitzman, Andrew; Sperry, Jason; Gallaher, Jared; Neff, Lucas; Sun, Yankai; Miller, Preston; Chang, Michael
Abstract Background The staged laparotomy in the operative management of emergency general surgery (EGS) patients is an extension of trauma surgeons operating on this population. Indications for its application, however, are not well defined, and are currently based on the lethal triad used in physiologically-decompensated trauma patients. This study sought to determine the acute indications for the staged, rapid source control laparotomy (RSCL) in EGS patients. Methods All EGS patients undergoing emergent staged RSCL and non-RSCL over 3 years were studied. Demographics, physiologic parameters, perioperative variables, outcomes, and survival were compared. Logistic regression models determined the influence of physiologic parameters on mortality and postoperative complications. EGS-RSCL indications were defined. Results 215 EGS patients underwent emergent laparotomy; 53 (25 %) were staged RSCL. In the 53 patients who underwent a staged RSCL based on the lethal triad, adjusted multivariable regression analysis shows that when used alone, no component of the lethal triad independently improved survival. Staged RSCL may decrease mortality in patients with preoperative severe sepsis / septic shock, and an elevated lactate (≥3); acidosis (pH ≤ 7.25); elderly (≥70); male gender; and multiple comorbidities (≥3). Of the 162 non-RSCL emergent laparotomies, 27 (17 %) required unplanned re-explorations; of these, 17 (63 %) had sepsis preoperatively and 9 (33 %) died. Conclusions The acute physiologic indicators that help guide operative decisions in trauma may not confer a similar survival advantage in EGS. To replace the lethal triad, criteria for application of the staged RSCL in EGS need to be defined. Based on these results, the indications should include severe sepsis / septic shock, lactate, acidosis, gender, age, and pre-existing comorbidities. When correctly applied, the staged RSCL may help to improve survival in decompensated EGS patients.